Vascular pathology associated with Leptospira icterohaemorrhagiae serovar Lai strain Langkawi infection in guinea pigs (Cavia porcellus) - Tyagita, G. H.; Bahaman, Abdul Rani; Sabri, Jasni; Hussein, Fuzina Nor; Tengku Ibrahim, Tengku Azmi (Veterinary Association Malaysia, 2018)
Fifteen (15) guinea pigs were experimentally infected with Leptospira icterohemorrhagiae serovar Lai strain Langkawi, a new strain that was isolated from a human leptospirosis patient. Hematoxylin and Eosin ((H&E) staining showed haemorrhages, congestion and oedema in all internal organs examined (lungs, liver, spleen and kidneys) with inflammatory cell infiltration characterized by neutrophils, lymphocytes and macrophages. Hydropic degeneration and cell necrosis were also common in our findings. Leptospires were detected starting Day 2 p.i by silver staining and Transmission Electron Microscopy (TEM). Rise in antibody titres started on Day 5 p.i and leptospiral DNA was detected beginning Day 3 in the kidneys and Day 5 in the liver by Polymerase Chain Reaction (PCR) assay. The findings illustrated the pathogenesis of leptospirosis in guinea pigs which disclosed them as a suitable animal model for demonstration of clinical symptoms of leptospirosis and pathological changes after being infected with Leptospira icterohaemorrhagiae serovar Lai strain Langkawi, particularly pulmonary haemorrhages, a leading cause of mortality in human leptospirosis.